Comparing Critical ThinkingDispositions of Students Enrolled In a College LevelGlobal SeminarCourse - Dennis W. Duncan; Rainer Haas; John C. Ricketts (Journal of International Agricultural and Extension Education, 2016)
In recent years, the discussion concerning critical thinking and problem solving among college graduates and new industry hires has increased dramatically. A plethora of research has discovered that college graduates entering the workforce are lacking in their ability to problem solve and think critically. These attributes have been called some of the most necessary for an individuals’ success in the 21stcentury. The purpose of this study was to identify the variance in critical thinking dispositionof students (undergraduate and graduate) enrolled in an International course (Global Seminar) using the UF-EMI Critical Thinking Disposition Assessment. Students representing the US, Italy, and Austria participated in this study (N=43). Results indicate that the entire population fell within the typical ranges for UF-EMI scores for all three constructs (Engagement, Cognitive Maturity, and Innovativeness) but would be classified as weak overall. There was however a slight difference in mean scores when comparing the US and European students. American students scored higher than the Italian studentsfor all three constructs and higher than the Austrian students for the Engagement and Innovativeness constructs. These results warrant further research to determine how course content, teaching methodologies, and experiential learning opportunities impact college students’ critical thinking dispositions.
Keywords: leadership; critical thinking; international education; agriculture